The Performance of Socially Responsible Investments - Milica Latinovic; Tijana Obradovic (Entrepreneurial Business and Economics Review, 2013)
The paper aims to annotate how selection of equity securities can be made by incorporating sustainability into analysis, and to present review of performance evidence of such an investment strategy.